URDU TEXTBOOKS WRITTEN UNDER SNC AND LINGUISTIC PROBLEMS - Sheema Saadia; Prof. Dr. Fouzia Aslam (Zaban-o-Adab, 2022)
Man and language are inevitably linked to each other. Man is a social animal whereas language is the outcome of social needs. Every language has a basic structure, with the assistance of which it makes its way to the road of development. Apart from the stages of origin and development of the language, if we take a bird’s eye view of its journey in 21st century we get to know that Urdu has been facing many linguistic problems. Linguist have varying opinions regarding the rules and terms of the language which is one of the reasons of lack of having language-related knowledge. Moreover, teachers being ignorant of fundamentals of language and language accuracy in textbooks create puzzlement in the young minds. Textbooks play a pivotal part in becoming proficient in language. So, it is mandatory to have perfectly design and accurate textbooks. Single National Curriculum 2020 for Urdu emphasizes on having textbooks free of misinterpretations and errors. The following article draws attention towards various linguistic problems in Urdu Textbooks that need rectification.